EFFECT OF SOIL CONDITIONS ON DAMAGE LEVELS TO SIDODADI ROAD, NGANTRU VILLAGE, NGANTANG DISTRICT, MALANG REGENCY - Rifky Aldila P.; Andy Kristafi A. (Journal Innovation of Civil Engineering (JICE), 2020)
Soil conditions as a foundation and greatly affect the quality of service and road construction conditions. This condition occurs in Ngantru Village, Ngantang District, Malang Regency which is the object of research. The research objectives include knowing the characteristics of the soil, knowing the effect of soil conditions on road damage and knowing the solution to the problem of road damage due to soil conditions. The data in this study include primary data and secondary data. The results of the study include the average value of the plasticity index of 0.60% <10% with silt soil type and the plasticity index value of 6% and the average moisture content value of 33.3%, the average CBR value of 8.20%. CBR average of 8.20%, so it can be concluded that the soil condition affects the road damage. The solution in this research is to repair the road by excavating the damaged part of the road.